Analyzing Hijab Fashion Purchase Intentions Using the Stimulus-Organism-Response (S-O-R) Model - Najib, Moh Farid; Fauziah, Tia; Purwihartuti, Koernia; Razli, Izyanti Awang (International Journal of Islamic Business and Economics (IJIBEC), 2024)
This study investigates the determinants of Muslim women's purchase intention for premium hijabs through the lens of the Stimulus-Organism-Response (S-O-R) framework. The research delves into the direct and mediated effects of hedonic value, utilitarian value, and religiosity on purchase intention, with attitude functioning as a mediating construct. By deploying the S-O-R model, the study captures the nuanced interplay between affective and cognitive dimensions of consumer decision-making processes. Employing an explanatory survey methodology, the research conducted a quantitative analysis involving 412 Muslim women in West Java, Indonesia. Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings reveal that both utilitarian and hedonic values exert statistically significant influences on purchase intention, while religiosity demonstrates an indirect impact on purchase behavior through attitudinal mediation. Critically, attitudes emerge as a substantive mediating mechanism in the relationship between these constructs and purchase intention. The results suggest that emotional satisfaction and perceived utility constitute more potent determinants of hijab purchasing behavior than religiosity in isolation. This study makes a substantive contribution to the scholarly discourse on Islamic consumer behavior by extending the application of the S-O-R model and providing nuanced, actionable insights for marketers within the modest fashion industry. The research opens avenues for future comparative investigations across Muslim-majority and minority contexts.